Essential oils for treating anxiety: a systematic review of randomized controlled trials and network meta-analysis - Tan, Ling; Liao, Fei-fei; Long, Lin-zi; Ma, Xiao-chang; Peng, Yu-xuan; Lu, Jie-ming; Qu, Hua; Fu, Chang-geng (Frontiers in Public Health, 2023)
Background and purpose: The findings of clinical studies exploring essential oils (EOs) for anxiety remain disputed, and no studies have yet clarified the differences in the efficacy of EOs. The purpose of the study was to directly or indirectly compare the effectiveness of different types of EOs on anxiety by pooling the results of randomized controlled trials (RCTs). Methods: PubMed, Cochrane Library, Embase, Scopus, Web of Science and CENTRAL databases were searched from inception to November 2022. Only full texts of RCTs that investigated the effects of EOs on anxiety were included. The trial data were extracted and the risk of bias was assessed by two reviewers independently. Pairwise meta-analysis and network meta-analysis were performed by Stata 15.1 or R 4.1.2 software. Results: Forty-four RCTs (fifty study arms) involving 10 kinds of EOs and 3419 anxiety patients (1815 patients in EOs group and 1604 patients in control group) were included. Pairwise meta-analyses showed that EOs were effective in reducing State Anxiety Inventory scores (SAIS) (WMD = -6.62, 95%CI -8.17, -5.08) and Trait Anxiety Inventory scores (TAIS) (WMD = -4.96, 95%CI -6.73, -3.20). Additionally, EOs could decrease systolic blood pressure (SBP) [WMD = -6.83, 95%CI (-10.53, -3.12), P < 0.001] and heart rate (HR) [WMD = -3.43, 95%CI (-5.51, -1.36), P < 0.001]. Network meta-analyses demonstrated that regarding the outcome of SAIS, jasmine was the most effective with a weighted mean difference (WMD) of -13.56 (95%CrI -24.45, -2.66). Followed by citrus aurantium L., which had a WMD of -10.53 (95%CrI -14.34, -6.74). Moderate effect sizes were observed for damask rose (WMD = -6.77, 95%CrI -10.07, -3.55) and lavender (WMD = -5.45, 95%CrI -7.88, -3.09). Regarding the results of TAIS, citrus aurantium L. was the best ranked intervention with a WMD of -9.62 (95%CrI -15.62, -3.7). Moderate-to-large effect sizes were observed for lemon (WMD: -8.48; 95%CrI -16.67, -0.33) and lavender (WMD: -5.5; 95%CrI -8.7, -2.46). Conclusion: EOs are effective in reducing both state anxiety and trait anxiety, and citrus aurantium L. essential oil seems to be the most recommended type of EO for treating anxiety.